Digital strategies for museum dissemination in the era of COVID-19. a comparative study between Ecuador, Spain and Peru - Longhi-Heredia, Sebastián-Alberto (2021)
The communication strategies implemented by the museums after the COVID-19 health crisis implied the closure of the institutions to the public. Hence the need to contrast how Ecuador, Spain and Peru acted by highlighting the culture and heritage available to the population. The exploratory study was approached through mixed content analysis. The actions implemented by museums in the context of the pandemic were classified and they categorized, taking into account the type of content and resources deployed to reach the public. Finally, focus was placed on identifying UNESCO’s strategic areas of action. The supranational trend registered changes depending on the situation of each country. In this sense, it was noted that the actions deployed from Spain were in line with international reports. From Ecuador and Peru, the ‘Digital Activities’ and the ‘Activities on Social Networks’ turned out to be more representative than the average described by the reports. At the thematic level, the content disseminated was mostly of a communicational and educational nature, with topics related to research and preservation being relegated.